New 3-O-substituted xanthone derivatives as promising acetylcholinesterase inhibitors - Zi Han Loh; Huey Chong Kwong; Kok Wai Lam; Soek Sin Teh; Gwendoline Cheng Lian Ee; Ching Kheng Quah; Anthony Siong Hock Ho; Siau Hui Mah (Taylor & Francis Group, 2021)
A new series of 3-O-substituted xanthone derivatives were synthesised and evaluated for their anti-cholinergic activities against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). The results indicated that the xanthone derivatives possessed good AChE inhibitory activity with eleven of them (5, 8, 11, 17, 19, 21-23, 26-28) exhibited significant effects with the IC50 values ranged 0.88 to 1.28 µM. The AChE enzyme kinetic study of 3-(4-phenylbutoxy)-9H-xanthen-9-one (23) and ethyl 2-((9-oxo-9H-xanthen-3-yl)oxy)acetate (28) showed a mixed inhibition mechanism. Molecular docking study showed that 23 binds to the active site of AChE and interacts via extensive π-π stacking with the indole and phenol side chains of Trp86 and Tyr337, besides the hydrogen bonding with the hydration site and π-π interaction with the phenol side chain of Y72. This study revealed that 3-O-alkoxyl substituted xanthone derivatives are potential lead structures, especially 23 and 28 which can be further developed into potent AChE inhibitors.